2019
DOI: 10.1016/j.applthermaleng.2018.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the contaminant distribution with improved ventilation system in hospital isolation rooms: Effect of supply and exhaust air diffuser configurations

Abstract: Expected risk of infection from patients to healthcare workers in an AIIR was found.• We investigated how to remove airborne contamination effectively in AIIRs.• Both full-scale field experiments and CFD simulations were performed. • Transport of gaseous pollutants is indicated by tracer gas.• By changing the exhaust air flow, the exposure pollutant level was significantly reduced. A B S T R A C TThis study, that is practice-based learning in a real hospital construction project, has evaluated the ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 20 publications
0
43
0
3
Order By: Relevance
“…In earlier studies, pathogen transmission has been investigated widely in various indoor environments ( Li et al, 2007 , Morawska et al, 2017 , Ai and Melikov, 2018 ). In many cases, CFD and experimental studies have been conducted to examine the airborne transmission in simplified environments ( Yu et al, 2004 , Zhang and Chen, 2006 , Liu et al, 2017 ) that may have an association with ventilation ( Li et al, 2005 , Olmedo et al, 2012 , Cao et al, 2015 ), airflow interaction ( Bivolarova et al, 2017 , Li et al, 2018a , Ai et al, 2019 ), in hospitals ( Yu et al, 2005 , King et al, 2015 , Cho, 2019 ) and offices ( He et al, 2011 ). Certain studies also consider transport induced by human motion ( Edge et al, 2005 , Han et al, 2014 ) as well as breathing, talking and coughing ( Gupta et al, 2010 , Licina et al, 2015 , Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, pathogen transmission has been investigated widely in various indoor environments ( Li et al, 2007 , Morawska et al, 2017 , Ai and Melikov, 2018 ). In many cases, CFD and experimental studies have been conducted to examine the airborne transmission in simplified environments ( Yu et al, 2004 , Zhang and Chen, 2006 , Liu et al, 2017 ) that may have an association with ventilation ( Li et al, 2005 , Olmedo et al, 2012 , Cao et al, 2015 ), airflow interaction ( Bivolarova et al, 2017 , Li et al, 2018a , Ai et al, 2019 ), in hospitals ( Yu et al, 2005 , King et al, 2015 , Cho, 2019 ) and offices ( He et al, 2011 ). Certain studies also consider transport induced by human motion ( Edge et al, 2005 , Han et al, 2014 ) as well as breathing, talking and coughing ( Gupta et al, 2010 , Licina et al, 2015 , Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that a negative-pressure OR addresses many of these concerns [ 10 ]. The negative pressure inside the OR was maintained at a negative pressure of 4.7 Pa or greater, and the air introduced from the perforated supply diffuser from the ceiling was discharged through an exhaust grill located at a height of 110 cm from the floor at all four corners of the OR [ 11 ] ( Fig. 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four modelling studies demonstrated how to minimise the contamination of airflows in respiratory disease isolation rooms. One found that directing fresh airflows from the ceiling over the patient's bed and exhausting airflows through the wall behind the bed caused the least contamination of a manikin representing an HCW standing in front of the patient to provide care [82]. A study of contamination from door opening as a manikin representing an HCW entered from an anteroom found sliding doors reduced contamination compared to opening doors [83].…”
Section: Increasing the Use Of Medical Or Surgical Masks And Hand Hygiene To Reduce The Transmission Of Respiratory Virusesmentioning
confidence: 99%